Urban variety in social housing context in Costa Rica - von Breymann, Helga (2023)
In Costa Rica, as in other Latin American countries, recent socio-spatial dynamics reveal the exclusion processes that have generated land market trends. Population groups that have required social housing have seen limited opportunities to access them in accessible and well-endowed urban areas. On the contrary, they have had to go to live in the residential peripheries; homogeneous areas of little variety and complexity, little accessible and with significant deficiencies, seeing limited forms of access to well-being. This study analyzes the urban variety of two areas where Social Housing Projects have been built in recent years. The data, compiled from institutional sources and collected from field work, allow the generation of indices to assess the socioeconomic variety of the population, the variety of physical support and the variety of uses and activities in the contexts studied. The results show that the residential complexes present important shortcomings in the different dimensions of the urban variety, and that the areas where they have been built offer their inhabitants limited options to access services, commerce, transport, etc., reaffirming the socio-spatial exclusion tendencies for the most vulnerable population groups.